Dating Violence and Help-Seeking Behaviour among Adolescent Undergraduates of Obafemi Awolowo University - S. A., Oluwatosin; A. A., AKINWALE (Advances in Social Sciences Research Journal, 2018)
The study investigated dating violence and help-seeking behaviour among adolescent undergraduates of Obafemi Awolowo University. Using descriptive survey, an instrument, “Dating Violence and Help-Seeking Behaviour” was used to collect data from 591 students and data collected were analyzed using descriptive and inferential statistics. The study concluded that undergraduate adolescents experience dating violence and mostly in the form of emotional violence and they seek informal source of help which may account for under-reporting and hinder provision of appropriate formal source of help such as counselling intervention. It is recommended that school counsellors should try and sensitise the students about dating violence. University authorities need to implement strategies that encourage reporting of dating violence and ensure that reports are managed appropriately.